2010
DOI: 10.1186/1471-2164-11-168
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome survey of the anhydrobiotic tardigrade Milnesium tardigradum in comparison with Hypsibius dujardini and Richtersius coronifer

Abstract: BackgroundThe phenomenon of desiccation tolerance, also called anhydrobiosis, involves the ability of an organism to survive the loss of almost all cellular water without sustaining irreversible damage. Although there are several physiological, morphological and ecological studies on tardigrades, only limited DNA sequence information is available. Therefore, we explored the transcriptome in the active and anhydrobiotic state of the tardigrade Milnesium tardigradum which has extraordinary tolerance to desiccati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 79 publications
4
48
0
1
Order By: Relevance
“…Of the recognisable sequences, those in the stress and protein homeostasis categories are likely to be the most relevant to anhydrobiosis, including LEA protein, antioxidant, DNA repair, molecular chaperone and protein clearance genes. Therefore, although we are clearly only sampling a subset of the desiccome, bdelloids follow a pattern of gene expression observed in other dehydrating anhydrobiotes, principally nematodes (Adhikari et al, 2009;Gal et al, 2003;Reardon et al, 2010;Tyson et al, 2007) and tardigrades (Mali et al, 2010;Schill et al, 2004). Nevertheless, evidence for the involvement of non-reducing disaccharides in bdelloid rotifers is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the recognisable sequences, those in the stress and protein homeostasis categories are likely to be the most relevant to anhydrobiosis, including LEA protein, antioxidant, DNA repair, molecular chaperone and protein clearance genes. Therefore, although we are clearly only sampling a subset of the desiccome, bdelloids follow a pattern of gene expression observed in other dehydrating anhydrobiotes, principally nematodes (Adhikari et al, 2009;Gal et al, 2003;Reardon et al, 2010;Tyson et al, 2007) and tardigrades (Mali et al, 2010;Schill et al, 2004). Nevertheless, evidence for the involvement of non-reducing disaccharides in bdelloid rotifers is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, experimental approaches that identified genes upregulated by dehydration were first established in the resurrection plants (Bartels, 2005;Illing et al, 2005) and have more recently been implemented in invertebrates, primarily in tardigrades (Mali et al, 2010) and nematodes (Gal et al, 2003;Reardon et al, 2010;Tyson et al, 2007). Studies of this type could be particularly informative in bdelloid rotifers, as the anhydrobiology of these aquatic micro-invertebrates has unusual aspects: besides their lack of non-reducing disaccharides, the bdelloid LEA proteins defined to date are not especially hydrophilic and can exhibit secondary structure in solution (Pouchkina-Stantcheva et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…All are small (tardigrades are usually classified in the meiofauna) and are found in sediments and on vegetation from the Antarctic to the Arctic, from mountain ranges to the deep sea, and in marine and fresh water environments. Their dispersal may be associated with the ability of many (but not all) species to enter cryptobiosis, losing almost all body water, and resisting extremes of temperature, pressure, and desiccation (6)(7)(8)(9), deep space vacuum (10), and irradiation (11). Interest in tardigrades focuses on their utility as environmental and biogeographic markers, the insight their cryptobiotic mechanisms may yield for biotechnology and medicine, and exploration of their development compared with other Ecdysozoa, especially Nematoda and Arthropoda.…”
mentioning
confidence: 99%
“…H. dujardini has become a genomic model system, revealing the pattern of ecdysozoan phylogeny (3,4) and the evolution of small RNA pathways (23). H. dujardini is poorly cryptobiotic (24), but serves as a useful comparator for good cryptobiotic species (9).…”
mentioning
confidence: 99%
“…Many studies on evolutionarily distant organisms have shown that genes related to oxidative stress response are up-regulated during the desiccation process (Ingram and Bartels 1996;Browne et al, 2004;Oliver et al, 2004;Adhikari et al, 2009;Förster et al, 2009Förster et al, , 2012Cornette et al, 2010;Gusev et al, 2010;Mali et al, 2010;Schokraie et al, 2010Schokraie et al, , 2012 and that tolerance to desiccation is correlated with an increase in the amount of antioxidant molecules and antioxidant activity ( Figs. 2 and 3; Jiang and Zhang, 2002;Kranner and Birtić, 2005;França et al, 2007;Rizzo et al, 2010).…”
Section: Antioxidantsmentioning
confidence: 99%